People of the Morning Star : a novel of North America's forgotten past - Gear, W. Michael; Gear, Kathleen O'Neal (Gear, W. Michael. Morning star., 2014)
A religious miracle: the Cahokians believed that the divine hero Morning Star had been resurrected in the flesh. But not all is fine and stable in glorious Cahokia. To the astonishment of the ruling clan, an attempt is made on the living god's life. Now it is up to Morning Star's aunt, Matron Blue Heron, to keep it quiet until she can uncover the plot and bring the culprits to justice. If she fails, Cahokia will be torn asunder in warfare, rage, and blood as civil war consumes them all.